Leptogomphus tioman sp. nov. (Odonata: Anisoptera: Gomphidea) from Tioman Island, Peninsular Malaysia - Choong, Chee Yen (Zootaxa, 2016)
A new species Leptogomphus tioman is described based on male specimens collected from Tioman Island, Peninsular Malaysia. It is close to Leptogomphus risi Laidlaw in thoracic markings but is readily distinguished by its anal appendages and accessory genitalia.